Experimental Investigation of the Temperature Distribution along the Two-Phase Thermosyphon Height and the Condensation Type on the Top Cover; AIP Conference Proceedings; Vol. 2337 : Thermophysical Basis of Energy Technologies (TBET 2020) - Ponomarev K. O. Konstantin Olegovich (Technical thermal physics and nuclear energy, 2021)
Title screen